La Comédie-Française ou L'amour joué - Wiseman, Frederick; Davey, John (Frederick Wiseman - Intégrale Vol. 3: 1995-2016, 2016)
La Comédie-Française is the oldest continuous repertory company in the world, founded in Paris in the late 17th century. This is the first time a documentary film-maker has been allowed to look at all the aspects of the work of this great theatrical company. Sequences in the film include sections of plays, casting, set and costume design, administrative meetings and rehearsals and performances of four classic French plays, "Don Juan" by Molière, "La Thebaide" by Racine, "La Double Inconstance" by Marivaux and "Occupe-toi d'Amelie" by Feydeau. [www.zipporah.com]